SEISMICITY AND TECTONICS OF THE FAR WESTERN ALEUTIAN ISLANDS - Newberry J.T.; Laclair D.L.; Fujita K. (My University, 1986)
Study of focal mechanisms of earthquakes in the Near and Komandorsky Islands indicate that there are several distinct zones of tectonic activity. South of the Near Islands, normal faulting occurs in the trench east of 172°E and low-angle thrusting dominates the Aleutian ridge. Mechanisms indicate underthrusting as far west as Mednyy Island with strike-slip faulting restricted to the south and west of Beringa Island. A zone of northeast striking left-lateral faulting near 1645.°E is proposed to separate the Aleutian Ridge from Kamchatka Peninsula. This motion, as well as faulting north of the Komandorsky Islands, may be related to the existance of a buffer plate comprising the Aleutian Ridge in the Komandorsky Islands. Active subduction terminates near 173°E and the faulting north of the Komandorsky Islands may, in part, be due to the bouyancy of a remnant slab. Depth phase modelling indicates bulletin-reported depths are overestimated due to a misidentification of depth phases.